1984
DOI: 10.1111/j.1469-8137.1984.tb03576.x
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Endomycorrhizal Root Systems V. The Detailed Pattern of Development of Infection and the Control of Infection Level by Host in Young Leek Plants

Abstract: Summary Leek plants (Allium porrum L.) were grown on partly sterilized soil, in tall pots so that roots grew downwards unimpeded, with inoculum of the vesicular‐arbuscular mycorrhizal fungus Glomus mosseae (Nicol. & Gerd.) Gerdemann & Trappe placed either under the seedling or dispersed uniformly throughout the soil. The age of each individual root, and the distribution of infection in single roots were both determined in each of a series of sequential harvests. The development of the root systems was unaffect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
1

Year Published

1986
1986
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 9 publications
1
39
1
Order By: Relevance
“…According to this criterion, we investigated the changes in arbuscule life cycles after P treatment concerning the developmental stages of the youngest 10 intracellular colonizations in each infection front. Gradual development of arbuscules can be observed in this region (Buwalda et al, 1984) allowing the precise observation of P inhibition during colonization stages. The numbers of young arbuscules in infection fronts of P-treated roots tended to be decreased compared to those of watertreated roots.…”
Section: P Rapidly Reduces Arbuscule Density In Hyphal-colonized Regionsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to this criterion, we investigated the changes in arbuscule life cycles after P treatment concerning the developmental stages of the youngest 10 intracellular colonizations in each infection front. Gradual development of arbuscules can be observed in this region (Buwalda et al, 1984) allowing the precise observation of P inhibition during colonization stages. The numbers of young arbuscules in infection fronts of P-treated roots tended to be decreased compared to those of watertreated roots.…”
Section: P Rapidly Reduces Arbuscule Density In Hyphal-colonized Regionsmentioning
confidence: 99%
“…The term "colonized region" was used in reference to hyphal-colonized root regions and single colonized regions were bound by two infection fronts comprising intercellular hyphae (Supplemental Fig. S1; Buwalda et al, 1984). Numerous infection units can coalesce to form a colonized region, where the border of each infection unit is not identified at least within a few days from the beginning of colonization (Sanders and Sheikh, 1983).…”
Section: P Rapidly Reduces Arbuscule Density In Hyphal-colonized Regionsmentioning
confidence: 99%
“…(b)] after day 16. Earlier both host and fungus grew at constant but different relative growth rates until fractional infection reached a maximum, when the relative growth rates of both the total and infected root length became approximately equal, as observed by Buwalda et al (1984). Increase in infected length on the primary root and its laterals together was almost linear with time [ Fig.…”
Section: Total and Infected Root Lengthmentioning
confidence: 95%
“…2 (a), (b)], but the rate of extension of infection on the main axis itself declined from day 20 onwards. Buwalda et al (1984) have shown that infection by vesicular-arbuscular mycorrhizal fungi normally occupies discrete lengths of root bounded by advancing 'fronts', which they term 'infection segments'. In this experiment, the primary root encountered two layers of inoculum, 3 cm apart, hence there were two infection segments with four fronts formed initially.…”
Section: Total and Infected Root Lengthmentioning
confidence: 99%
See 1 more Smart Citation